Market access, price policy and diversification in Indian agriculture - Negi, Digvijay S.; Birthal, Pratap Singh; Roy, Devesh; Hazrana, Jaweriah (Indira Gandhi Institute of Development Research, 2020)
This paper provides empirical evidence of a causal relationship between the access to markets and the crop partial policies on the pattern of specialization or diversification in Indian agriculture. We uniquely combine highly spatially disaggregated data on cropping patterns, amenities, and market size at a granular level, and construct a measure of market access using indicators from both the supply and the demand side of trade. We employ the heteroscedasticity based two-stage Lewbel (2012) estimator to address the possible endogeneity of market access and also test for non-linearity between market access and crop diversification. Our results show that locations connected with bigger markets are more diversified into vegetables, and cash crops like oilseeds and cotton. However, the effect of market access moderates after a threshold level of diversification probably because of the non-market constraints. Nonetheless, the policy-induced distortions in agri-food markets, the nucleus of policies in the form of procurement of cereals mainly rice and wheat at the government-determined pre-announced minimum support prices, significantly attenuates the effect of market access on crop diversification.